2012
DOI: 10.1152/ajpheart.00438.2012
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation and mechanotransduction control the arteriolar response to small changes in hematocrit

Abstract: Here, we present an analytic model of arteriolar mechanics that accounts for key autoregulation mechanisms, including the myogenic response and the vasodilatory effects of nitric oxide (NO) in the vasculature. It couples the fluid mechanics of blood flow in arterioles with solid mechanics of the vessel wall and includes the effects of wall shear stress- and stretch-induced endothelial NO production. The model can be used to describe the regulation of blood flow and NO transport under small changes in hematocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
2
14
0
1
Order By: Relevance
“…The predicted values of [NO] are within 5% of the experimental observations reported in (47). This figure provides a quantitative justification for the assumption of a linear relationship between [NO] and τ , which is routinely used in microcirculation models (see, e.g., (67) and the references therein). While this relationship is clearly nonlinear, it can Figure 4: (A) Predicted (line) and observed (symbols) dependence of NO production rate on WSS.…”
Section: Model Validationsupporting
confidence: 78%
See 1 more Smart Citation
“…The predicted values of [NO] are within 5% of the experimental observations reported in (47). This figure provides a quantitative justification for the assumption of a linear relationship between [NO] and τ , which is routinely used in microcirculation models (see, e.g., (67) and the references therein). While this relationship is clearly nonlinear, it can Figure 4: (A) Predicted (line) and observed (symbols) dependence of NO production rate on WSS.…”
Section: Model Validationsupporting
confidence: 78%
“…Concentrations of both NO and cGMP increase with WSS. Over a broad range of WSS this increase is highly non-linear, but within the physiologically relevant ranges of WSS (around 20 dynes/cm 2 ) one can use a linear relation between [NO] and WSS(47,49,67).…”
mentioning
confidence: 99%
“…In a recent study by Sriram and co-workers (Sriram et al, 2012), the regulatory response of arterioles to small changes in hematocrit was predicted by using a two-phase fluid model. The relation between systemic hematocrit and CFL width was utilized for their simulation to predict changes in the NO transport and autoregulatory response.…”
Section: Resultsmentioning
confidence: 99%
“…may also contribute to the endothelial protective effect. On the other hand, it has been reported that there is a potential relationship between hematocrit and vascular function (Sriram et al, 2012).…”
Section: Discussionmentioning
confidence: 99%